Therapeutic mechanism of Fructus corni for diabetic kidney disease - Lou Wen-feng; Zhang Ning; Bu Tian-jie (Linchuang shenzangbing zazhi)
Objective To explore the therapeutic mechanism of Fructus corni for diabetic kidney disease（DKD）using network pharmacology researches.Methods For mining of active ingredients, Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform（TCMSP）and Swiss Target Prediction platform were accessed for retrieving the DKD-related targets in Online Mendelian Inheritance in Man（OMIM）,Therapeutic Target Database（TTD）,Gene Cards and Drug Bank.String platform was constructed for protein-protein interaction（PPI）.Cytoscape was utilized for GO and KEGG pathways and DAVID for enrichment analysis.Results A total of 20 compounds were screened.Among which, iridoid glycoside and genkwanin hydroxy compound predominated.There were key targets for PIK3 R1,EGFR,AKT1,PTGS2 and PTGS1.And 108 pathways were involved, including insulin resistance, pancreatic secretion and signal pathways of Rap1,HF-1 and VEGF.Conclusion It provides theoretical rationales for further studies of the potential mechanism of active ingredients of Fructus corni for DKD.